COMPARATIVE ASSESSMENT OF RATIONAL ANTIBIOTIC USAGE AMONG NON-PHYSICIAN HEALTH PROFESSIONALS AND LAY INDIVIDUALS - Ersan Gürsoy; Mehmet Vatansever (Journal of Medical Education and Family Medicine)
ABSTRACTObjective: Antibiotic resistance is a serious public health problem caused by the incorrect and excessive use of antibiotics. The aim of this study is to compare the habits, knowledge and attitudes towards antibiotic use among non-physician healthcare professionals and lay people Methods: This cross-sectional study, conducted in a family medicine clinic between November 2023 and January 2024, involved 329 participants aged 18-65 years, including non-physician healthcare workers and people visiting the clinic for various reasons. Participants were given a 13-item questionnaire to assess antibiotic use and a 19-item "Antibiotic Use Scale". Results: The mean age of the participants was 37.89±11.16 years. It was found that demographic characteristics such as gender, age, marital status, education level, income level, and tobacco and alcohol consumption had no significant effect on attitudes towards antibiotic use. The study showed that healthcare workers and people who preferred to visit a healthcare facility for upper respiratory tract infections tended to have more negative attitudes towards antibiotic use (p=0.021 and p<0.001 respectively). Conclusion: The results highlight the need for healthcare professionals to be more cautious in the use of antibiotics and underline the importance of comprehensive education and awareness programs for the general population. Considering that demographic characteristics do not have a significant impact on attitudes towards antibiotic use, educational efforts in this area should be accessible and effective for everyone.